KAJIAN POTENSI AIR DAN PENGEMBANGAN SUMBERDAYA AIR DAS SEMBAYAT (PENGEMBANGAN WILAYAH UTARA KABUPATEN GRESIK) - Dian Noorvy Khaerudin (Universitas Tribhuwana Tunggadewi, 2007)
A study that was aimed to analyze the potency of surface water for water resource development of the Gresik Regency was conducted by analyzing available rainfall and water discharge data. Results of this study showed the occurrence of water potency deficit and water shortage. Discharge of water from river flowing through the Gresik Regency did not originally come from excessive rainfall but it came from sea water flowing into the river at certain months, and from upstream and midstream discharges of Bengawan Solo river. Climate affected conditions of water resource potency which its main source is rainfall. Hence water supply could not be relied only from rainfall. The existing surface water can only provide 50% of the water need of the Gresik Regency for domestic uses and other 50% for industrial purposes. The remaining water need should be sought from other sourves such as drilling well, small basins and lakes